PEMBANGUNAN DAN TRANSFORMASI BUDAYA DALAM OTONOMI DAERAH - Miswardi, Miswardi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2011)
We believe that development with leaving the local values, will make it -development- will not survive during the time (won’t be sustainable). Therefore, a development must can respons local culture and values so that that development can be responship and can be continuable. It can be done if the society felts that a development is a collective responsibility. Now, Indonesia has very high probability to realize it, as autonomy is given to region -district- by central government.